(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the influence of family relationships on the child’s mental development, child upbringing in the family, factors influencing the child’s development, and every relationship in the family leaves its mark on the child’s upbringing.